17‐α estradiol ameliorates age‐associated sarcopenia and improves late‐life physical function in male mice but not in females or castrated males. Issue 2 (10th February 2019) - Garratt, Michael; Leander, Danielle; Pifer, Kaitlyn; Bower, Brian; Herrera, Jonathan J.; Day, Sharlene M.; Fiehn, Oliver; Brooks, Susan V.; Miller, Richard A.
Abstract: Pharmacological treatments can extend mouse lifespan, but lifespan effects often differ between sexes. 17‐α estradiol (17aE2), a less feminizing structural isomer of 17‐β estradiol, produces lifespan extension only in male mice, suggesting a sexually dimorphic mechanism of lifespan regulation. We tested whether these anti‐aging effects extend to anatomical and functional aging—important in late‐life health—and whether gonadally derived hormones control aging responses to 17aE2 in either sex. While 17aE2 started at 4 months of age diminishes body weight in both sexes during adulthood, in late‐life 17aE2‐treated mice better maintain body weight. In 17aE2‐treated male mice, the higher body weight is associated with heavier skeletal muscles and larger muscle fibers compared with untreated mice during aging, while treated females have heavier subcutaneous fat. Maintenance of skeletal muscle in male mice is associated with improved grip strength and rotarod capacity at 25 months, in addition to higher levels of most amino acids in quadriceps muscle. We further show that sex‐specific responses to 17aE2—metabolomic, structural, and functional—are regulated by gonadal hormones in male mice. Castrated males have heavier quadriceps than intact males at 25 months, but do not respond to 17aE2, suggesting 17aE2 promotes an anti‐aging skeletal muscle phenotype similar to castration. Finally, 17aE2 treatment benefits can be recapitulated in mice when treatment is started at 16 months, suggesting that 17aE2 may be able to improve aspects of late‐life function even when started after middle age.